Bullying and depression among adolescents in East Asia: a scoping review on prevalence rates, risk and protective factors - Kiing, Jennifer Sie Hee; Ragen, Elizabeth Sarah; Sulaiman, Mohamed Sufyan Bin Mohmed; Goh, Wei Sheng; Tan, Norman Jun Hao; Ng, Sok Hui; Luo, Yang; Samuel, Miny; Young, Doris; Loh, Victor Weng Keong (Frontiers in Psychiatry, 2025)
IntroductionBullying and victimization in adolescence is associated with mental health problems including depression. Depression in East Asian adolescents presents similarities and differences from that in Western adolescents. This review reports on the prevalence and psychosocial associations of bullying and depression in East Asian adolescents.MethodsElectronic databases (Medline, and Embase) were searched for English language articles on bullying and its associations for a span of 10 years (1st January 2013 to 19th January 2024). Searches were limited to studies conducted in East Asia involving adolescents 10-19 years of age.ResultsOut of 1,231 articles initially identified, 65 full-text articles (consisting of 44 cross-sectional and 21 cohort studies) met the inclusion criteria and were included for qualitative synthesis & analysis. Prevalence rates of bullying ranged from 6.1% - 61.3% in traditional bullying victimization and 3.3% to 74.6% in cyberbullying victimization with higher rates in at-risk groups (e.g., adolescents with internet addiction). Psychosocial associations of bullying and depression which were similarly found in Western cultures include individual factors of coping style and gender; family factors of functioning and sibling relationships; and community factors of friendship and school-connectedness. In contrast, unique East Asian risk factors included being different (i.e., sexual minority status) and teachers as bullies.ConclusionFindings of this scoping review suggest that strong relationships within families, peers and the school community coupled with adolescents’ positive coping style are protective against the negative effects of bullying. Conversely, poor parent-child attachment in the midst of family dysfunction, poor engagement with peers and the school community together with low self-esteem predispose East Asian adolescents to depressive symptoms as a result of victimization. Similar to Western cultures, adolescents who are bully-victims and poly-victims are most vulnerable to depression. As a significant proportion of bullying occurred in school, future research could focus on a whole-school intervention approach to counter bullying.